O trabalho de campo e a educação ambiental na formação continuada de professores - Berezuk, Paulo Augusto (2015)
The importance of Environmental Education for the scientific and citizen formation has presented a huge increasing in the last decades due to the intense environmental degradation in the planet. Because of this concerning, there are teachers from several levels of teaching who are working with Environmental themes on their classes. However, although the Environmental Education is essential for students' formation, this sort of teaching still deals with strong resistance if you consider its development as an actual transformation proposal in schools nowadays. This kind of situation provokes the decreasing and even the lack of lessons on Fieldwork, for the teaching practice. Furthermore, it also prevents students from having the opportunity of witnessing the complexity, the diversity and the extent of the natural phenomena. Thus, this research has investigated how the Fieldwork is inset in the Environmental Education, which is developed by teachers. Moreover, this research contributes with the continuing education of teachers, and it helps therefore with the improvement of teaching quality at schools. For this, we developed a qualitative and quantitative research type, and we divided it in two parts: interviewing teachers, and carrying out with a short-term course. We interviewed twenty-nine teachers from different subjects and from schools previously chosen in order to obtain the data for the first part of this research. We worked with a ten-question semi-structured questionnaire. The data analysis has been developed based on the analysis method of contents. The obtained data from the interviews has guided us to create themes we worked during the short-term course. We developed the analysis of this short-term course by the observation of the participants' behavior and speeches. Furthermore, the obtained data from the activities proposed was also analyzed in order to find out the participants' previous knowledge, as well as if it had been improved throughout the course. We could conclude that few teachers work with themes related to Sustainable Development, and none of the teachers have declared they work with the Critical Environmental Education theme. Almost every interviewed teachers have declared that they work with Environmental Education contents in their classes. However, they are much dependent on lectures and lessons without students participation for developing their approach. Considering the Fieldwork, we observed that the interviewed teachers have shown lack of knowledge. Moreover, during the short-term course, teachers have reported they did not know what are social representations and its connections to Environmental Education, as well as information about international and national histories of Environmental Education. We could also noticed that many teachers use to elaborate their Fieldwork plannings in an incomplete way, spoiling its application. In fact, several difficulties caused the decreasing of the frequency of fieldworks, as lack of financial resources and pedagogical support in schools as well. From discussions and practical activities, the short-term course could provide for most participants a changing related to their conceptions, causing an improvement on their knowledges about Environmental Education and also about Fieldwork.